Towards a wearable monitoring tool for in-field ice hockey skating performance analysis - Stetter, B. J.; Buckeridge, E.; Nigg, S. R.; Sell, S.; Stein, T. (European Journal of Sport Science, 2019)
The capturing of movements by means of wearable sensors has become increasingly popular in order to obtain sport performance measures during training or competition. The purpose of the current study was to investigate the feasibility of using body worn accelerometers to identify previous highlighted performance related biomechanical changes in terms of substantial differences across skill levels and skating phases. Twenty-two ice hockey players of different caliber were equipped with two 3D accelerometers, located on the skate and the waist, as they performed 30 m forward skating sprints on an ice rink. Two measures of the temporal stride characteristics (contact time and stride time) and one measure of the propulsive power (stride propulsion) of a skating stride were calculated and checked for discriminating effects across (i) skill levels and (ii) sprint phases as well as for their (iii) strength of association with the sprint performance (total sprint time). High caliber players showed an increased stride propulsion (+22%, P < 0.05) and shorter contact time (-5%, P < 0.05). All three analysed variables highlighted substantial biomechanical differences between the accelerative and constant velocity phases (P < 0.05). Stride propulsion of acceleration strides primarily correlated to total sprint time (r = -0.57, P < 0.05). The results demonstrate the potential of accelerometers to assess skating technique elements such as contact time or elements characterizing the propulsive power such as center of mass acceleration, to gauge skating performance. Thus, the findings of this study might contribute to establishing wearable sensors for in-field ice hockey skating performance analysis.